Electrochemical hydrogen charging device and nanoindentation test method for hydrogen-charged metal materials

By designing an electrochemical hydrogen charging device and a nano-indentation test method for hydrogen-filled metal materials, the problems of cumbersome operation and inaccurate data in the prior art were solved, and safe and simple multiple hydrogen charging and nano-indentation tests were realized on the metal materials, and accurate experimental data were obtained.

CN115753286BActive Publication Date: 2025-05-02CHINA SHIP SCIENTIFIC RESEARCH CENTER
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211490131.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-05-02
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

When the prior art studies the interaction between hydrogen and the microstructure of the internal microstructure of metal materials, the operation is complicated and easy to damage the sample, resulting in inaccurate experimental data.

Method used

An electrochemical hydrogen charging device and a nano-indentation test method for hydrogen charging metal materials were designed. By setting a combined structure of a protective block and a cathode wire, repeated hydrogen charging and nano-indentation tests for the same sample were realized, simplifying the operation process and obtaining sufficient experimental data.

Benefits of technology

This method simplifies the operation process, ensures that the sample state is not destroyed, obtains accurate and scientific experimental data, and can perform multiple repetitive experiments on the same sample.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115753286B_ABST
    Figure CN115753286B_ABST
Patent Text Reader

Abstract

The present invention relates to an electrochemical hydrogen charging device and a nano-indentation test method for hydrogen-charged metal materials, comprising a sample, a protective block and an electrolytic cell. The protective block is a block structure, and a groove opening upward is provided on the upper surface of the protective block. The sample is embedded in the groove. The protective block also comprises a cathode wire, one end of which passes through the protective block and is connected to the sample, and the other end of the cathode wire is connected to a direct current power supply. The nano-indentation test method comprises sample annealing, wire welding and sample embedding, polishing the protective block embedded with the sample, placing the protective block embedded with the sample in an electrolytic cell containing an electrolyte to hydrogenate the sample, and then performing a nano-indentation test on the sample, and then performing low-temperature dehydrogenation on the combined structure of the protective block, the sample and the cathode wire as a whole. The same sample can be repeatedly charged with hydrogen and subjected to a nano-indentation test, the operation process is simplified, and sufficient experimental data is obtained without destroying the state of the sample, so that the experimental data is accurate and scientific.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material hydrogen embrittlement performance analysis, in particular to an electrochemical hydrogen charging device and a nano-indentation test method for hydrogen-charged metal materials. Background Art

[0002] Hydrogen embrittlement refers to the phenomenon that the strength of metals or alloys decreases and premature fracture occurs due to hydrogen penetration. Hydrogen can easily enter the interior of metal materials during the preparation and processing of metal materials and the production and transportation of hydrogen energy. The existence of the hydrogen embrittlement problem has greatly challenged the safety of metal material applications. It is generally believed that the interaction between hydrogen and microscopic defects inside metal materials is the main cause of hydrogen embrittlement. Therefore, exploring the interaction mechanism between hydrogen and microscopic defects inside metal materials is the main direction of studying the hydrogen embrittlement problem.

[0003] Nanoindentation test is one of the most useful methods for studying the micromechanical mechanism of materials and is widely used to study the interaction mechanism between hydrogen and the internal microstructure of metal materials. Due to the large randomness of the microstructure, when using nanoindentation equipment to study the interaction between hydrogen and a certain microstructure inside the material, it is necessary to perform multiple nanoindentation tests near the same microstructure of the same sample to ensure the consistency of the test results. Since the range available for testing near the internal microstructure of the material is very small, it is necessary to repeat the surface polishing-hydrogenation-nanoindentation test-dehydrogenation operation on the same sample many times to obtain sufficient test data.

[0004] The traditional pre-hydrogenation test method and in-situ hydrogenation test method do not consider the situation that the test object needs to be repeatedly hydrogenated. The operation process is cumbersome and easily damages the surface of the sample, and the experimental data is inaccurate. Therefore, a safe and simple metal material nanoindentation test method is needed, which can perform multiple hydrogenation tests on the material to obtain sufficient and accurate test data to meet the subsequent analysis of the test results. Summary of the invention

[0005] In view of the shortcomings of the above-mentioned existing production technology, the applicant provides an electrochemical hydrogen charging device and a nanoindentation test method for hydrogen-charged metal materials, thereby realizing repeated hydrogen charging and nanoindentation testing on the same sample, simplifying the operation process and obtaining sufficient experimental data without destroying the sample state, making the experimental data accurate and scientific.

[0006] The technical solution adopted by the present invention is as follows:

[0007] An electrochemical hydrogen charging device comprises a sample, a protection block and an electrolytic cell, wherein the protection block is a block structure, a groove opening upward is provided on the upper surface of the protection block, and the sample is embedded in the groove, and further comprises a cathode wire, one end of the cathode wire passes through the protection block and is connected to the sample, and the other end of the cathode wire is connected to a DC power supply;

[0008] The electrolytic cell contains electrolyte, the protective block containing the sample is immersed in the electrolyte, and a platinum counter electrode is also arranged in the electrolytic cell, the lower end of the platinum counter electrode is immersed in the electrolyte, and the upper end of the platinum counter electrode is connected to a DC power supply through an anode wire.

[0009] As a further improvement of the above technical solution:

[0010] The raw materials for making the protection block include epoxy resin and curing agent in a mass ratio of 2:1.

[0011] One end of the cathode wire passes through the side of the protection block and is connected to the bottom of the sample.

[0012] The guard block is formed by a die, and the specimen is located at the center of the guard block.

[0013] A method for nanoindentation testing of hydrogen-charged metal materials comprises the following steps:

[0014] Sample annealing: Place the sample in a high temperature furnace for high temperature annealing;

[0015] Wire welding and sample embedding: weld one end of the cathode wire to the annealed sample, then embed the sample into the protection block, and let the cathode wire pass through the protection block;

[0016] Mechanical polishing of the sample surface: The protective block with the sample embedded in it is embedded in the grinding and polishing machine, and the surface of the sample to be tested is mechanically polished;

[0017] Electrolytic polishing of the sample surface: After the sample surface is mechanically polished, the protective block with the sample embedded is placed in the electrolytic polishing liquid for electrolytic polishing treatment;

[0018] When the sample surface is electrolytically polished and needs to be hydrogenated, the sample is hydrogenated, that is, the protective block with the sample embedded is placed in an electrolytic cell containing an electrolyte, a platinum counter electrode connected to an anode wire is placed in the electrolyte, and the cathode wire and the anode wire are connected to a DC power supply and powered on;

[0019] After the sample is filled with hydrogen, a nano indentation test is performed on the sample. Since the sample is filled with hydrogen, after the nano indentation test is completed, the combined structure of the protection block, the sample and the cathode wire is subjected to low-temperature dehydrogenation of the sample as a whole.

[0020] As a further improvement of the above technical solution:

[0021] When the sample surface is electrolytically polished and there is no need to charge the sample with hydrogen, the nanoindentation test is directly performed. Since the sample is not charged with hydrogen, the sample surface is mechanically polished directly after the nanoindentation test is completed.

[0022] For the samples after the nanoindentation test and low-temperature dehydrogenation, mechanical polishing of the sample surface, electrolytic polishing of the sample surface, hydrogen filling of the sample, nanoindentation test, and low-temperature dehydrogenation of the sample are repeated.

[0023] When the sample is dehydrogenated at low temperature, the hydrogen-filled sample is placed in a high-temperature furnace for dehydrogenation treatment. The sample is placed in a high-temperature furnace at a temperature of 60°C-150°C for 2 hours-4 hours, and then taken out of the high-temperature furnace after the sample is naturally cooled.

[0024] The temperature of the high temperature furnace is 80°C, and the sample is placed in the high temperature furnace at 80°C for 3 hours.

[0025] The sample embedding method is: place the sample with the test surface facing downward into the mold, pour the prepared raw material for making the protective block into the mold, and lead the cathode wire out of the mold from the side of the mold, let it stand for a while to wait for the raw material for making the protective block in the mold to solidify, and then remove the mold to obtain the protective block containing the sample.

[0026] The beneficial effects of the present invention are as follows:

[0027] The invention has a compact and reasonable structure and is easy to operate. By arranging a protection block structure capable of leading out a cathode wire of a sample, the combined structure of the protection block, the sample and the cathode wire is used as a whole to perform sample polishing, hydrogen charging, nanoindentation experiment and dehydrogenation, thereby eliminating the need for multiple embedding and de-embedding operations of the sample, facilitating multiple repetitive experiments on the same sample, obtaining sufficient experimental data and simplifying the operation process, without destroying the state of the sample, and making the experimental data accurate and scientific.

[0028] At the same time, the present invention also has the following advantages:

[0029] (1) In the structure of embedding the sample in the protection block, the raw materials of the protection block are epoxy resin and curing agent with a mass ratio of 2:1, which is convenient for mold forming operation. At the same time, the combined structure of the protection block, the sample and the cathode wire is dehydrogenated as a whole at a temperature of 60°C-150°C without destroying the embedding structure of the protection block;

[0030] (2) The nanoindentation test can be carried out on the same sample before hydrogen filling or after multiple dehydrogenation tests, and multiple blank tests can be performed, which provides a data basis for judging whether the device and operation during the test have an impact on the state of the sample, ensuring the scientific and accurate test process.

[0031] (3) The temperature of the high temperature furnace is 80°C, and the sample is placed in the high temperature furnace at 80°C for 3 hours. While ensuring that the material protection block and the sample embedding structure are not affected, the efficiency and effect of dehydrogenation are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic structural diagram of the electrochemical hydrogen charging device of the present invention.

[0033] Figure 2 It is a schematic structural diagram of the electrochemical hydrogen charging device of the present invention (the electrolytic cell is in a perspective state).

[0034] Figure 3 It is a schematic diagram of the structure of the protection block, sample and cathode wire of the present invention.

[0035] Figure 4 This is an exploded view of the protection block, sample and cathode wire of the present invention.

[0036] Figure 5 This is an exploded view of the protection block, sample and cathode wire of the present invention (from another perspective).

[0037] Figure 6 This is a flow chart of the nanoindentation test of hydrogen-charged metal materials of the present invention.

[0038] Figure 7 The load-indentation depth curve is obtained after the nanoindentation test near the same grain boundary is carried out on the sample made of polycrystalline nickel in Example 6 of the present invention at different stages of multiple hydrogen charging tests.

[0039] Among them: 1. electrolytic cell; 2. cover plate; 3. protective block; 4. sample; 5. platinum counter electrode; 6. cathode wire; 7. anode wire; 8. ventilation hole. DETAILED DESCRIPTION

[0040] The specific implementation of the present invention is described below in conjunction with the accompanying drawings.

[0041] like Figure 1-Figure 5 As shown, the electrochemical hydrogen charging device of the first embodiment includes a sample 4, a protection block 3 and an electrolytic cell 1, wherein the protection block 3 is a block structure, and a groove opening upward is provided on the upper surface of the protection block 3, and the sample 4 is embedded in the groove, and further includes a cathode wire 6, one end of the cathode wire 6 passes through the protection block 3 and is connected to the sample 4, and the other end of the cathode wire 6 is connected to a DC power supply;

[0042] The electrolytic cell 1 contains an electrolyte, and the protective block 3 containing the sample 4 is immersed in the electrolyte. The electrolytic cell 1 is also provided with a platinum counter electrode 5, the lower end of the platinum counter electrode 5 is immersed in the electrolyte, and the upper end of the platinum counter electrode 5 is connected to a DC power supply through an anode wire 7. The cathode wire 6 passes through the cover plate 2 and is electrically connected to the cathode of the DC power supply, and the anode wire 7 passes through the cover plate 2 and is electrically connected to the anode of the DC power supply. The cover plate 2 is provided with a ventilation hole 8.

[0043] On the one hand, the combined structure of the protection block 3, the sample 4 and the cathode wire 6 can be polished together before hydrogen charging, so that the operations during and after the polishing process do not affect the state of the sample 4, thereby improving the accuracy of the experiment. At the same time, the same sample 4 can also be polished multiple times, thereby improving the convenience of multiple experimental operations.

[0044] On the other hand, it is also convenient to perform the electrochemical hydrogen charging operation after dehydrogenation of the same sample 4 without removing the sample 4, which plays a protective role and improves the convenience of multiple experimental operations.

[0045] In order to facilitate the combination structure of the protection block 3, the sample 4 and the cathode wire 6 to perform multiple nanoindentation experiments after hydrogen charging, the protection block 3 and the sample 4 can be dehydrogenated at low temperature together to ensure that the same sample 4 can be polished, hydrogenated, nanoindented and dehydrogenated without destroying the embedded structure of the protection block 3, thereby simplifying the operation steps and obtaining more experimental data.

[0046] In the above operations, no operation outside the test conditions caused damage to the state of sample 4.

[0047] By setting up a protection block 3 structure that can lead out the cathode wire 6 of the sample 4, the combined structure of the protection block 3, the sample 4 and the cathode wire 6 can be used as a whole to perform sample polishing, hydrogen charging, nanoindentation experiment and dehydrogenation, which is convenient for performing multiple repetitive experiments on the same sample 4, obtaining sufficient experimental data and simplifying the operation process, without destroying the state of the sample 4, so that the experimental data is accurate and scientific.

[0048] The raw materials for making the protection block 3 include epoxy resin and curing agent in a mass ratio of 2:1.

[0049] One end of the cathode wire 6 passes through the side of the protection block 3 and is connected to the bottom of the sample 4 .

[0050] The protection block 3 is formed by a mold, and the sample 4 is located at the center of the protection block 3 .

[0051] In the structure of the sample 4 embedded in the protection block 3, the raw materials of the protection block 3 are epoxy resin and curing agent with a mass ratio of 2:1, which is convenient for mold forming operation. At the same time, the combined structure of the protection block 3, the sample 4 and the cathode wire 6 is dehydrogenated as a whole at a temperature of 60°C-150°C without destroying the embedded structure of the protection block 3. Because the sample 4 is generally thin, the cathode wire 6 is connected to the bottom of the sample 4 for easy operation. The cathode wire 6 passes through the side of the protection block 3 to facilitate the clamping of the protection block 3 in the grinding and polishing machine.

[0052] like Figure 6 As shown, the nanoindentation test method for hydrogen-charged metal materials of embodiment 2 comprises the following steps:

[0053] Sample annealing: Sample 4 is placed in a high temperature furnace for high temperature annealing treatment;

[0054] Wire welding and sample embedding: weld one end of the cathode wire 6 to the annealed sample 4, then embed the sample 4 into the protection block 3, and the cathode wire 6 passes through the protection block 3;

[0055] The sample embedding method is as follows: put the sample 4 with the test surface facing downward into the mold, pour the prepared raw material for making the protection block 3 into the mold, and lead the cathode wire 6 out of the mold from the side of the mold, wait for a period of time for the raw material for making the protection block 3 in the mold to solidify, and then take off the mold to obtain the protection block 3 containing the sample 4;

[0056] Furthermore, the raw materials of the protective block 3 are epoxy resin and curing agent in a volume ratio of 2:1;

[0057] Mechanical polishing of the sample surface: the protective block 3 inlaid with the sample 4 is embedded in the grinding and polishing machine, and the surface of the sample 4 to be tested is mechanically polished;

[0058] Electrolytic polishing of the sample surface: After the sample surface is mechanically polished, the protective block 3 inlaid with the sample 4 is placed in an electrolytic polishing solution for electrolytic polishing treatment;

[0059] When the sample surface is electrolytically polished and the sample 4 needs to be hydrogenated, the sample is hydrogenated, that is, the protective block 3 embedded with the sample 4 is placed in the electrolytic cell 1 containing the electrolyte, the platinum counter electrode 5 connected with the anode wire 7 is placed in the electrolyte, and the cathode wire 6 and the anode wire 7 are connected to the DC power supply and powered on;

[0060] After the sample is charged with hydrogen, a nano indentation test is performed on the sample 4. Since the sample 4 is charged with hydrogen, after the nano indentation test is completed, the combined structure of the protection block 3, the sample 4 and the cathode wire 6 is subjected to low-temperature dehydrogenation of the sample.

[0061] After the combined structure of the protection block 3, the sample 4 and the cathode wire 6 is subjected to low-temperature dehydrogenation of the sample as a whole, subsequent steps such as mechanical polishing of the sample surface and electrolytic polishing of the sample surface can be carried out.

[0062] The sample 4 can be polished, charged with hydrogen, and subjected to nanoindentation tests while maintaining the overall structure of the combination of the protection block 3, the sample 4, and the cathode wire 6, and the overall dehydrogenation of the combination structure can be achieved. The same sample 4 can be subjected to multiple nanoindentation tests, or multiple nanoindentation tests after hydrogen charging, eliminating the need for multiple embedding and de-embedding operations of the sample 4, achieving multiple repetitive experiments while being simple to operate. In the processes other than polishing, the state of the sample 4 is not changed due to operations other than the test conditions, thus ensuring that the experimental data are accurate and scientific.

[0063] like Figure 6 As shown, the nanoindentation test method for hydrogen-charged metal materials of embodiment 3 comprises the following steps:

[0064] First case:

[0065] Sample annealing: Sample 4 is placed in a high temperature furnace for high temperature annealing treatment;

[0066] Wire welding and sample embedding: weld one end of the cathode wire 6 to the annealed sample 4, then embed the sample 4 into the protection block 3, and the cathode wire 6 passes through the protection block 3;

[0067] Mechanical polishing of the sample surface: the protective block 3 inlaid with the sample 4 is embedded in the grinding and polishing machine, and the surface of the sample 4 to be tested is mechanically polished;

[0068] Electrolytic polishing of the sample surface: After the sample surface is mechanically polished, the protective block 3 inlaid with the sample 4 is placed in an electrolytic polishing solution for electrolytic polishing treatment;

[0069] When the sample surface is electrolytically polished and there is no need to charge hydrogen to the sample 4, the nanoindentation test is directly performed. Since the sample 4 is not charged with hydrogen, the sample surface is directly mechanically polished after the nanoindentation test is completed.

[0070] The above is the nanoindentation test before hydrogen charging.

[0071] Second case:

[0072] Sample annealing: Sample 4 is placed in a high temperature furnace for high temperature annealing treatment;

[0073] Wire welding and sample embedding: weld one end of the cathode wire 6 to the annealed sample 4, then embed the sample 4 into the protection block 3, and the cathode wire 6 passes through the protection block 3;

[0074] Mechanical polishing of the sample surface: the protective block 3 inlaid with the sample 4 is embedded in the grinding and polishing machine, and the surface of the sample 4 to be tested is mechanically polished;

[0075] Electrolytic polishing of the sample surface: After the sample surface is mechanically polished, the protective block 3 inlaid with the sample 4 is placed in an electrolytic polishing solution for electrolytic polishing treatment;

[0076] When the sample surface is electrolytically polished and the sample 4 needs to be hydrogenated, the sample is hydrogenated, that is, the protective block 3 embedded with the sample 4 is placed in the electrolytic cell 1 containing the electrolyte, the platinum counter electrode 5 connected with the anode wire 7 is placed in the electrolyte, and the cathode wire 6 and the anode wire 7 are connected to the DC power supply and powered on;

[0077] After the sample is charged with hydrogen, a nano indentation test is performed on the sample 4. Since the sample 4 is charged with hydrogen, after the nano indentation test is completed, the combined structure of the protection block 3, the sample 4 and the cathode wire 6 is subjected to low-temperature dehydrogenation of the sample.

[0078] Then, the surface of the sample is mechanically polished again: the protection block 3 inlaid with the sample 4 is embedded in the grinding and polishing machine, and the surface of the sample 4 to be tested is mechanically polished;

[0079] Electrolytic polishing of the sample surface: After the sample surface is mechanically polished, the protective block 3 inlaid with the sample 4 is placed in an electrolytic polishing solution for electrolytic polishing treatment;

[0080] When the sample surface is electrolytically polished and there is no need to charge hydrogen to the sample 4, the nanoindentation test is directly performed. Since the sample 4 is not charged with hydrogen, the sample surface is directly mechanically polished after the nanoindentation test is completed.

[0081] The above is the first nanoindentation test after dehydrogenation. After the nanoindentation test after multiple hydrogen charging is completed and dehydrogenation is performed, the sample 4 can be polished and then subjected to nanoindentation test again.

[0082] The above method realizes the nanoindentation test on the same sample 4 before hydrogen charging or after multiple hydrogen removals, and can realize multiple blank tests, which provides a data basis for judging whether the device and operation during the test process have an impact on the state of the sample 4, and ensures the scientific and accurate test process.

[0083] like Figure 6 As shown, the nanoindentation test method for hydrogen-charged metal materials of embodiment 4 comprises the following steps:

[0084] Sample annealing: Sample 4 is placed in a high temperature furnace for high temperature annealing treatment;

[0085] Wire welding and sample embedding: weld one end of the cathode wire 6 to the annealed sample 4, then embed the sample 4 into the protection block 3, and the cathode wire 6 passes through the protection block 3;

[0086] Mechanical polishing of the sample surface: the protective block 3 inlaid with the sample 4 is embedded in the grinding and polishing machine, and the surface of the sample 4 to be tested is mechanically polished;

[0087] Electrolytic polishing of the sample surface: After the sample surface is mechanically polished, the protective block 3 inlaid with the sample 4 is placed in an electrolytic polishing solution for electrolytic polishing treatment;

[0088] When the sample surface is electrolytically polished and the sample 4 needs to be hydrogenated, the sample is hydrogenated, that is, the protective block 3 embedded with the sample 4 is placed in the electrolytic cell 1 containing the electrolyte, the platinum counter electrode 5 connected with the anode wire 7 is placed in the electrolyte, and the cathode wire 6 and the anode wire 7 are connected to the DC power supply and powered on;

[0089] After the sample is filled with hydrogen, a nano indentation test is performed on the sample 4. Since the sample 4 is filled with hydrogen, after the nano indentation test is completed, the combined structure of the protection block 3, the sample 4 and the cathode wire 6 is subjected to low-temperature dehydrogenation of the sample as a whole;

[0090] For sample 4 which was subjected to low temperature dehydrogenation after the nanoindentation test, mechanical polishing of the sample surface, electrolytic polishing of the sample surface, hydrogenation of the sample, nanoindentation test, and low temperature dehydrogenation of the sample were repeated.

[0091] Nanoindentation tests after multiple hydrogen filling of the same sample 4 are realized, eliminating the need for multiple embedding and de-embedding operations of the sample 4, not destroying the state of the sample 4, simplifying the operation process, obtaining sufficient experimental data, and making the experimental data accurate and scientific.

[0092] In the nanoindentation test method for hydrogen-charged metal materials of Example 5, when the samples in Examples 2 and 3 are dehydrogenated at low temperature, the hydrogen-charged sample 4 is placed in a high-temperature furnace for dehydrogenation treatment. The sample 4 is placed in a high-temperature furnace at a temperature of 60°C-150°C for 2 hours-4 hours, and then the sample 4 is taken out of the high-temperature furnace after it is naturally cooled.

[0093] When the temperature of the high temperature furnace is 60°C, the sample 4 is placed in the high temperature furnace at 60°C for 4 hours.

[0094] When the temperature of the high temperature furnace is 150° C., the sample 4 is placed in the high temperature furnace at 150° C. for 2 hours.

[0095] The temperature of the high temperature furnace is preferably 80° C., and the sample 4 is placed in the high temperature furnace at 80° C. for 3 hours. While ensuring that the embedded structure of the material protection block 3 and the sample 4 is not affected, the efficiency and effect of dehydrogenation are improved.

[0096] In addition, in the above steps:

[0097] Sample annealing is mainly used to reduce the residual stress and internal defect density of the sample;

[0098] When the sample surface is mechanically polished, it is first roughly polished with sandpaper, and then finely polished with a polishing suspension containing fine particles; the particle size of the suspension gradually decreases from 9μm to 0.05μm.

[0099] When the sample surface was electropolished, the electropolishing solution was 1 mol / L sulfuric acid solution, the electropolishing voltage was 30 V, and the electropolishing time was 2 minutes.

[0100] When the sample is charged with hydrogen, different electrolyte solutions are prepared for different test materials, such as: the electrolyte concentration is 0.05 mol / L; the pH value of the electrolyte is 6; the current density is set to 1.4-2.3 mA / cm 2 .

[0101] When the sample is charged with hydrogen, the charging time shall not be longer than 20 minutes.

[0102] After the hydrogen filling of the sample is completed, the surface to be tested of the sample 4 is quickly air-dried, and then the protection block 3 containing the sample 4 is placed in the nanoindenter for testing;

[0103] The test time of sample 4 after the sample is filled with hydrogen shall not be longer than 30 minutes.

[0104] The method for nanoindentation testing of hydrogen-charged metal materials in Example 6 is based on the example of performing multiple hydrogen-charged nanoindentation tests near the same grain boundary in polycrystalline nickel in a Hysitron 980Tribo nanoindenter. The specific implementation method is as follows:

[0105] (i) The sample 4 made of high-purity (99.99%) polycrystalline nickel used in the test is a small circular thin sheet with a height of and a radius of. It is placed in a high-temperature furnace, and the temperature in the furnace is raised to, and the temperature is maintained for 6 hours. Then, the sample 4 is kept in the furnace to cool naturally to room temperature, and a high-temperature annealing treatment is performed to reduce the residual stress and internal defect density of the sample 4;

[0106] (ii) Welding the other side of the sample 4 opposite to the surface to be tested to one end of the cathode wire 6, then placing the sample 4 with the surface to be tested facing downward into the mold, then pouring the epoxy resin and curing agent with a volume ratio of 2:1 into the mold, and leading the other end of the cathode wire 6 out of the mold from the side of the mold, leaving it to stand for a period of time to wait for the epoxy resin and curing agent in the mold to solidify, and then removing the mold to obtain the protective block 3 containing the sample 4;

[0107] (iii) inserting the protective block 3 containing the sample 4 into a grinding and polishing machine, and performing mechanical polishing on the surface to be tested of the sample 4, firstly rough polishing with sandpaper of 600 to 2000 mesh, then fine polishing with a polishing suspension containing diamond particles, and finally final mechanical polishing with a suspension containing silicon dioxide nanoparticles;

[0108] (iv) After mechanically polishing the surface to be tested of the sample 4, the protective block 3 containing the sample 4 is placed in an electrolytic polishing instrument, a sulfuric acid solution is used as an electrolytic polishing liquid, the polishing voltage is set to, and the surface to be tested of the sample 4 is electrolytically polished for 2 minutes;

[0109] (V) firstly perform a nanoindentation test on the sample 4 that has not been charged with hydrogen, and place the protection block 3 containing the sample 4 into the nanoindenter for testing, to obtain nanoindentation test data before the first hydrogen charging;

[0110] (vi) repeating steps (iii) to (iv) to obtain a polished sample 4 again;

[0111] (VII) preparing a solution as an electrochemical hydrolysis hydrogenation electrolyte, and adjusting the pH value of the solution to 6, first introducing the electrolyte into the electrolytic cell 1, and then respectively placing the protection block 3 connected to the cathode wire 6 and the platinum counter electrode 5 connected to the anode wire 7 into the electrolyte, and then respectively connecting the cathode wire 6 to the cathode of the DC power supply, and connecting the anode wire 7 to the anode of the DC power supply, adjusting the current density to, turning on the power switch to charge the sample 4 with hydrogen for 15 minutes;

[0112] (VIII) After the hydrogen charging is completed, the surface to be tested of the polycrystalline nickel sample 4 is quickly air-dried, and the protective block 3 containing the sample 4 is placed in a nanoindenter for testing. The test time is controlled within 30 minutes, and the nanoindentation test data after the first hydrogen charging is completed is obtained;

[0113] (IX) After the test is completed, the embedded structure 3 including the sample 4 is taken out from the nanoindenter, placed in a high temperature furnace, set the temperature to 80° C., maintained at this temperature for 3 hours, and taken out after it is naturally cooled;

[0114] (10) Repeat steps (3) to (5) to obtain nanoindentation test data after the first dehydrogenation;

[0115] (11) Repeat steps (3) to (4) and (7) to (9) multiple times to obtain nanoindentation test data after the second hydrogen charging and nanoindentation test data after multiple hydrogen charging of the same polycrystalline nickel sample.

[0116] like Figure 7 As shown, the load-indentation depth curves of the sample 4 made of polycrystalline nickel obtained after the nanoindentation test near the same grain boundary at different stages in multiple hydrogen charging tests:

[0117] a is the curve before the first hydrogen filling;

[0118] b is the curve after the first hydrogen filling;

[0119] c is the curve after the first dehydrogenation;

[0120] d is the curve after the second hydrogen filling.

[0121] By comparing the curve a before the first hydrogen charging and the curve b after the first hydrogen charging, it can be seen that the indentation load (the load when the displacement platform appears) of the sample 4 before the hydrogen charging is large, and the indentation load decreases significantly after the first hydrogen charging, which indicates that the hydrogen charging affects the local mechanical properties of the polycrystalline nickel.

[0122] By comparing the curve a before the first hydrogen charging and the curve c after the first dehydrogenation, it can be seen that after the first dehydrogenation, the indentation mutation load recovers to the load level before hydrogen charging;

[0123] By comparing the curve b after the first hydrogen charging and the curve d after the second hydrogen charging, it can be seen that the indentation mutation load decreases again after the second hydrogen charging;

[0124] The above two situations show that this hydrogen charging test method can repeatedly test the influence of hydrogen on the local mechanical properties of the material without causing damage to the sample itself. There is no change in the state of sample 4 due to operations outside the test conditions. At the same time, it provides a data basis for judging whether the device and operation during the test process have an impact on the state of sample 4, thereby ensuring the scientific and accurate test process.

[0125] While maintaining the overall structure of the combination of the protection block 3, the sample 4 and the cathode wire 6, the sample 4 is polished, hydrogen-charged, and subjected to nanoindentation experiments, and the overall dehydrogenation of the combination structure is performed. This allows the same sample 4 to be subjected to multiple nanoindentation tests, or multiple nanoindentation tests after hydrogen charging, eliminating the need for multiple embedding and de-embedding operations of the sample 4, achieving multiple repetitive experiments with simple operations, and providing accurate and scientific experimental data.

[0126] The above description is an explanation of the present invention, not a limitation of the present invention. The scope of the present invention is defined in the claims. Any form of modification may be made within the scope of protection of the present invention.

Claims

1. A method for nanoindentation testing of hydrogen-charged metal materials, characterized in that: The following steps are involved: Sample annealing: placing the sample (4) in a high temperature furnace for high temperature annealing treatment; Wire welding and sample embedding: welding one end of the cathode wire (6) to the annealed sample (4), then embedding the sample (4) into the protection block (3), and the cathode wire (6) passes through the protection block (3); Mechanical polishing of the sample surface: the protective block (3) inlaid with the sample (4) is embedded in a grinding and polishing machine, and the surface of the sample (4) to be tested is mechanically polished; Electrolytic polishing of the sample surface: After the sample surface is mechanically polished, the protective block (3) inlaid with the sample (4) is placed in an electrolytic polishing liquid for electrolytic polishing treatment; When the sample surface is electrolytically polished and the sample (4) needs to be hydrogenated, the sample is hydrogenated by placing the protective block (3) inlaid with the sample (4) into an electrolytic cell (1) containing an electrolyte, placing a platinum counter electrode (5) connected to an anode wire (7) into the electrolyte, and connecting the cathode wire (6) and the anode wire (7) to a DC power supply and energizing them; After the sample is charged with hydrogen, a nanoindentation test is performed on the sample (4). Since the sample (4) is charged with hydrogen, after the nanoindentation test is completed, the combined structure of the protection block (3), the sample (4) and the cathode wire (6) is subjected to low-temperature dehydrogenation of the sample as a whole; After the nanoindentation test, the sample (4) was subjected to low temperature dehydrogenation, and the sample surface mechanical polishing, sample surface electrolytic polishing, sample hydrogenation, nanoindentation test, and sample low temperature dehydrogenation were repeated.

2. The method for nanoindentation testing of hydrogen-charged metal materials according to claim 1, characterized in that: When the sample is dehydrogenated at low temperature, the sample (4) charged with hydrogen is placed in a high temperature furnace for dehydrogenation treatment. The sample (4) is placed in the high temperature furnace at a temperature of 60°C to 150°C for 2 hours to 4 hours, and then the sample (4) is taken out of the high temperature furnace after it is naturally cooled.

3. The method for nanoindentation testing of hydrogen-charged metal materials according to claim 2, characterized in that: The temperature of the high temperature furnace is 80°C, and the sample (4) is placed in the high temperature furnace at 80°C for 3 hours.

4. The method for nanoindentation testing of hydrogen-charged metal materials according to claim 1, characterized in that: The sample embedding method is as follows: the sample (4) is placed into a mold with the surface to be tested facing downward, the prepared raw material for making the protective block (3) is poured into the mold, and the cathode wire (6) is led out of the mold from the side of the mold, and the raw material for making the protective block (3) in the mold is allowed to solidify for a period of time, and then the mold is removed to obtain the protective block (3) containing the sample (4).

5. The method for nanoindentation testing of hydrogen-charged metal materials according to claim 1, characterized in that: The method uses an electrochemical hydrogen charging device, the device comprising a sample (4), a protection block (3) and an electrolytic cell (1), the protection block (3) being a block structure, the upper surface of the protection block (3) being provided with a groove opening upward, the sample (4) being embedded in the groove, and the device also comprising a cathode wire (6), one end of the cathode wire (6) passing through the protection block (3) and connected to the sample (4), and the other end of the cathode wire (6) being connected to a DC power supply; The electrolytic cell (1) contains an electrolyte, a protective block (3) containing a sample (4) is immersed in the electrolyte, and a platinum counter electrode (5) is also arranged in the electrolytic cell (1), the lower end of the platinum counter electrode (5) is immersed in the electrolyte, and the upper end of the platinum counter electrode (5) is connected to a DC power supply via an anode wire (7).

6. The method for nanoindentation testing of hydrogen-charged metal materials according to claim 5, characterized in that: The raw materials for making the protection block (3) include epoxy resin and curing agent in a mass ratio of 2:

1.

7. The method for nanoindentation testing of hydrogen-charged metal materials according to claim 5, characterized in that: One end of the cathode wire (6) passes through the side of the protection block (3) and is connected to the bottom of the sample (4).

8. The method for nanoindentation testing of hydrogen-charged metal materials according to any one of claims 5 to 7, characterized in that: The protection block (3) is formed by a mold, and the sample (4) is located at the center of the protection block (3).

Citation Information

Patent Citations

  • In-situ hydrogen-inflation experiment device

    CN110133090A

  • Electrochemical hydrogen charging device for metal sample

    CN204177648U